The Prospects of Islamic Microfinance: Maqasid Shariah Perspective - Hussein Azeemi bin Abdullah Thaidi; Muhamad Firdaus Ab Rahman; Azman Ab Rahman; Muhammad Aiman Fathi bin Shamsuri (Tazkia Islamic Finance and Business Review, 2022)
Islamic microfinance is one of the instruments that has been scientifically demonstrated to help the poor and needy. The instrument aims to help the underprivileged by giving them access to financing based on Shariah principles for lucrative activities, primarily small and micro-businesses. Notwithstanding that the Islamic microfinance providers claim that they comply with the Islamic rulings (hukm), little attention has been paid to the extent to which the practice addresses the maqasid (objectives) shariah. Such claim of Shariah-compliant practice will be rendered meaningless if maqasid shariah are not realised. Hence, the present paper aims to explore the significance and prospects of the Islamic microfinance practice from the standpoint of maqasid shariah. The library research, inductive, deductive and analytical techniques are employed consistently. The findings reveal that Islamic microfinance has a significant roles in realising the major maqasid shariah, namely: safeguarding the religion, human life, intellect wealth and progeny. These prospects convey the perception that much effort needs to be done to encourage the offering of Islamic microfinancial products at the Islamic finance sectors at large. Future studies may propose maqasid shariah guidelines for the better practice of Islamic microfinance. Keywords: Islamic Microfinance, Maqasid Shariah, Poor Population, Prospects